Analysis of Red Blood Cells and their Components in Medical Workers with Occupational Exposure to Low-Dose Ionizing Radiation - Xue-Lei Tian; Xue Lu; Yu-Min Lyu; Hua Zhao; Qing-Jie Liu; Mei Tian (SAGE Publishing, 2022)
Plenty of reports focus on the effects of low-dose radiation (LDR) on peripheral blood lymphocytes in radiation workers. However, studies on red blood cells (RBCs) in radiation workers are rarely reported. Many studies focused on investigate the hemogram of radiation staffs without detecting other components of RBCs. To explore the potential effect of LDR on RBCs, we detected the level of RBC count, hemoglobin, 2,3-disphosphoglycerate (2,3-DPG), and glutathione (GSH), and then analyzed the factors on these indices in 106 medical radiation workers. As a result, RBC count was affected by sex, age, type of work, length of service (only for females), and annual effective dose (only for males). Hemoglobin status was affected by sex, type of work, and annual effective dose (only for males). Sex, age, and type of work had no effects on the concentration of 2,3-DPG and GSH. Length of service affected 2,3-DPG concentration, and annual effective dose affected GSH level. In conclusion, chronic occupational LDR exposure may have an effect on RBC count, hemoglobin status, and the concentration of 2,3-DPG and GSH in radiation workers to some extent. However, it is still unknown how this kind of influence affects the health of radiation workers.